Su alcuni graffiti cristiani scoperti nella cappella bizantina delle Beatitudini a Tabgha - De Luca, Stefano (Liber annuus, 2010)
The Christian character of the inscription is undoubtable, as testified by the abbreviation of the invocation Kyrie Christe, and by the considerable number of crosses also engraved in the plaster by ancient pilgrims. Due to the poor state of preservation, the authors offer some interpretations for the other recognizable letters - apparently in capital Greek - on the base of the published epigraphic repertoires for the Near East.